Letter to the editor on “A review: Exploring the role of ChatGPT in the diagnosis and treatment of oral pathologies” - Naji Naseef Pathoor; Gopal Rajesh Kanna; Pitchaipillai Sankar Ganesh (Oral Oncology Reports)
The integration of ChatGPT in oral pathology diagnosis holds significant promise for enhancing various aspects of oral healthcare delivery. Drawing from research findings, ChatGPT's ability to provide precise answers to clinical questions is highlighted. Additionally, it explores AI's diverse applications in oral pathology, discussing challenges such as occasional inaccuracies and ethical considerations. Implications for education and innovation is also addressed. Overall, it offers valuable insights into ChatGPT integration in oral pathology diagnosis, guiding future research and implementation efforts.